2020
DOI: 10.1101/gad.337691.120
|View full text |Cite
|
Sign up to set email alerts
|

Collapse of the hepatic gene regulatory network in the absence of FoxA factors

Abstract: The FoxA transcription factors are critical for liver development through their pioneering activity, which initiates a highly complex regulatory network thought to become progressively resistant to the loss of any individual hepatic transcription factor via mutual redundancy. To investigate the dispensability of FoxA factors for maintaining this regulatory network, we ablated all FoxA genes in the adult mouse liver. Remarkably, loss of FoxA caused rapid and massive reduction in the expression of critical liver… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
40
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(44 citation statements)
references
References 43 publications
(63 reference statements)
3
40
1
Order By: Relevance
“…Conditional deletion of Foxa1 alone from DP thymocytes did not grossly affect αβT-cell development, and the double Foxa1/2cKO had a stronger impact on differentiation from DP to SP than the single Foxa2cKO, suggesting overlapping or redundant functions, so that although Foxa1 may not be required at this developmental transition it can partially replace the requirement for Foxa2. Foxa1 and Foxa2 have compensatory and partially redundant roles in other tissues, including liver ( Kaestner, 2010 ), and a recent study showed that conditional deletion of Foxa3 in addition to Foxa1 and Foxa2 in adult liver abrogated liver gene regulatory networks, destroying liver tissue homeostasis and function in the adult ( Reizel et al, 2020 ). It will therefore be important in the future to investigate the potential compensatory role of Foxa3 in T-cell development.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Conditional deletion of Foxa1 alone from DP thymocytes did not grossly affect αβT-cell development, and the double Foxa1/2cKO had a stronger impact on differentiation from DP to SP than the single Foxa2cKO, suggesting overlapping or redundant functions, so that although Foxa1 may not be required at this developmental transition it can partially replace the requirement for Foxa2. Foxa1 and Foxa2 have compensatory and partially redundant roles in other tissues, including liver ( Kaestner, 2010 ), and a recent study showed that conditional deletion of Foxa3 in addition to Foxa1 and Foxa2 in adult liver abrogated liver gene regulatory networks, destroying liver tissue homeostasis and function in the adult ( Reizel et al, 2020 ). It will therefore be important in the future to investigate the potential compensatory role of Foxa3 in T-cell development.…”
Section: Discussionmentioning
confidence: 99%
“…Foxa2-deficient embryos display severe defects in notochord, floorplate and endoderm and die at embryonic day (E) 10-11, whereas Foxa1-null mice exhibit defects in the regulation of glucose homeostasis and die postnatally ( Weinstein et al, 1994 ; Shih et al, 1999 ). Foxa1 and Foxa2 play overlapping and compensatory roles in the regulation of development of lung, liver and pancreas ( Kaestner, 2010 ; Gao et al, 2008 ; Reizel et al, 2020 ; Lee et al, 2005 ; Wan et al, 2005 ).…”
Section: Introductionmentioning
confidence: 99%
“…For instance, FOXA pioneer factors, which are already expressed in endodermal progenitor cells in the embryo and are essential for specification of the hepatic lineage, and allow subsequent promotion of hepatoblast differentiation by HNF4A [ 61 , 117 ]. A recent study in which Foxa genes were ablated in the adult mouse liver demonstrated that FOXA factors were additionally important to maintain HNF4A binding in terminally differentiated hepatocytes [ 118 ], contributing to HNF4′s role in cell identity maintenance. In line, during intestinal development, the pioneer-like factor CDX2 induces gut specification [ 119 ], while HNF4 factors are required for the next phase which is intestinal maturation through activation of fetal maturation genes [ 57 , 95 ].…”
Section: Mechanisms Of Action In the Control Of Cell Identity By Hmentioning
confidence: 99%
“…Foxc1 lacks a chromatin modifying domain (Yoshida et al, 2015) and therefore would need to interact with a co-factor to directly open chromatin. Foxc1 could also act to maintain open chromatin, as shown for Foxa1 in the liver (Reizel et al, 2020). Given that both Foxc1 and Sox9 have expression in many tissues outside the skeletal system, it will also be important to determine whether additional factors help to further restrict their activity to chondrocyte enhancers within skeletogenic mesenchyme.…”
Section: Resultsmentioning
confidence: 99%